The Proposed Implementation of Enterprise Architecture in E-Government Development and Services - Afarini, Nihayah; Hindarto, Djarot (International Journal Software Engineering and Computer Science (IJSECS), 2023)
The advancement of information technology has emerged as a significant driver in the paradigm shift of contemporary governance, wherein E-Government has emerged as a primary mechanism for delivering public services to the public in a more streamlined and adaptable fashion. To attain this objective, adopting Enterprise Architecture has surfaced as a foundational strategic methodology. Enterprise Architecture facilitates the planning, design, and development of integrated E-Government systems for governments, thereby ensuring the efficient and effective collaboration of diverse government entities. This study investigates the feasibility of incorporating Enterprise Architecture into the framework of E-Government advancement through an assessment of its advantages. Enterprise Architecture facilitates the integration of pre-existing government systems, the elimination of redundant resource allocations, and enhancing citizen services. Furthermore, by establishing a measurable and manageable framework for E-Government projects, Enterprise Architecture facilitates the implementation of the government's long-term objectives. Moreover, Enterprise Architecture is instrumental in safeguarding sensitive data and information, a critical function within the e-governance framework. This study incorporates successful case studies and best practices from numerous nations that have effectively integrated Enterprise Architecture into the development of electronic governments. The findings emphasize the critical function of Enterprise Architecture in expediting the process of E-Government conversion and providing advantages to various parties involved, such as the government, society, and private industry. This study offers E-Government stakeholders a practical guide for utilizing Enterprise Architecture to achieve substantial advancements in public services and more efficient government.